Teaching in Times of Crisis Through a Palliative Care Lens. Issue 5 (2nd September 2022) - Bigelow, April; Price, Deborah; Mason, Heidi; Harden, Karen
Abstract: The disruption of classroom and clinical education caused by the COVID-19 pandemic resulted in student distress and worry regarding the future of their education. Faculty trained in palliative care adapted the SPIKES mnemonic and applied it to real-time interactions with students in an effort to decrease distress and enable continued learning. Palliative care concepts, approaches, and techniques can be used to successfully facilitate faculty-student interactions during times of crisis and rapidly changing educational environments.